Lack of cell cycle regulation of telomerase activity in human cells - Holt, Shawn E. (The National Academy of Sciences of the USA, 1997)
Conflicting reports have appeared concerning the cell cycle regulation of telomerase activity and its possible repression during quiescence and cell differentiation. We have reexamined these issues in an attempt to uncover the basis for the discrepancies. Variations in extracted telomerase activity during the cell cycle are not observed in cells sorted on the basis of DNA content. Variations are observed in cells synchronized using some biochemical cell cycle inhibitors, but only with those agents where cellular toxicity is evident. A progressive decline in telomerase activity is observed in cells whose growth rate is reduced from seven to eight population doublings per week to one to two doublings per week. Telomerase is largely absent in cells that truly exit the cell cycle and do not divide over the 7-day period. Although it is not necessary for all cell types to regulate telomerase in the same way, we conclude that in the immortal cultured cell lines examined, extracted telomerase activity does not change significantly during progression through the stages of the cell cycle. Telomerase activity generally correlates with growth rate and is repressed in cells that exit the cell cycle and become quiescent.